Main Characters and Relief of the Ramayana Story at the Siwa Temple of Prambanan - Iskandar, Asep Deni (Universitas Negeri Medan, 2024)
The Ramayana story reliefs in the Prambanan temple, which are considered artifacts of the past, not only present information about the heroic Ramayana story, but also present a way of drawing that was considered modern at that time. The way of drawing done by the carvers is very distinctive, which is very different from the modern way of drawing or the Western naturalist-perspective-momentopname drawing system. With the typical way of drawing, the carvers can tell many events in one relief panel. The scenes depicted in the relief panels are the embodiment of selected scenes in the Old Javanese Ramayana literature. The transformation from literature into a relief story is similar to a movie derived from a novel. Filmic in the relief of the story can be seen in the selection of the right scene in the literature and the series of scenes arranged into a unified story. The carvers at that time tried to draw the character of each character according to their imagination and used a unique way of drawing. This way of drawing is used to examine the reliefs of the Ramayana story at Prambanan Shiva temple. This research uses qualitative methods and data is obtained through observation and literature review. Research to reveal how to draw the main character and the arrangement of each object based on the Old Javanese Ramayana literature. From the results of the analysis, it can be seen that the previous sculptors have described the character and relief depiction of the Ramayana story by adjusting to the existing literature.The Ramayana story reliefs in the Prambanan temple, which are considered artifacts of the past, not only present information about the heroic Ramayana story, but also present a way of drawing that was considered modern at that time. The way of drawing done by the carvers is very distinctive, which is very different from the modern way of drawing or the Western naturalist-perspective-momentopname drawing system. With the typical way of drawing, the carvers can tell many events in one relief panel. The scenes depicted in the relief panels are the embodiment of selected scenes in the Old Javanese Ramayana literature. The transformation from literature into a relief story is similar to a movie derived from a novel. Filmic in the relief of the story can be seen in the selection of the right scene in the literature and the series of scenes arranged into a unified story. The carvers at that time tried to draw the character of each character according to their imagination and used a unique way of drawing. This way of drawing is used to examine the reliefs of the Ramayana story at Prambanan Shiva temple. This research uses qualitative methods and data is obtained through observation and literature review. Research to reveal how to draw the main character and the arrangement of each object based on the Old Javanese Ramayana literature. From the results of the analysis, it can be seen that the previous sculptors have described the character and relief depiction of the Ramayana story by adjusting to the existing literature.